NON-ENGLISH MAJOR STUDENTS’ PERCEPTIONS: THE USE OF ENGLISH IN ENGLISH SUBJECT LEARNING - POYUNGI, YURIKE SUHERTIAN (PT Akselerasi Karya Mandiri, 2025)
As an English lecturer who presents and explains material using English in the class, it is important to know the students’ perceptions about this method. This article aims to discover students’ perceptions of the use of English in the English class. Data were collected through a questionnaire containing 15 questions which were close-ended. The result indicates that students prefer the lecturer to use Indonesian as the instruction language to explain grammar or vocabulary because it makes them feel more comfortable, understand better, more confident in the learning process. However, the lecture’s use of English did not significantly impact students’ motivation and participation to learn English.